Agency conflicts and short- versus long-termism in corporate policies - Gryglewicz, Sebastian; Mayer, Simon; Morellec, Erwan (Journal of Financial Economics, 2020)
We build a dynamic agency model in which the agent controls both current earnings via short-term investment and firm growth via long-term investment. Under the optimal contract, agency conflicts can induce short- and long-term investment levels beyond first best, leading to short- or long-termism in corporate policies. The paper analytically shows how firm characteristics shape the optimal contract and the horizon of corporate policies, thereby generating a number of novel empirical predictions on the optimality of short- versus long-termism. It also demonstrates that combining short- and long-term agency conflicts naturally leads to asymmetric pay-for-performance in managerial contracts.